PROSPECTS FOR THE DEVELOPMENT OF ECOLOGICAL TOURISM IN THE KHARKIV REGION - Svidlo, Karyna; Mamchenko, Lyudmila; Sokolenko, Anna (SWorld-Ger Conference proceedings, 2022)
In scientific practice, it is considered the prospects of greening the hotel business on the example of the 5-star Kharkiv Palace hotel. A comprehensive assessment of the benefits received by hotel enterprises around the world as a result of environmen